The immune evasion roles of Staphylococcus aureus protein A and impact on vaccine development - Bear, Alex; Locke, Thomas; Rowland-Jones, Sarah; Pecetta, Simone; Bagnoli, Fabio; Darton, Thomas C. (Frontiers in Cellular and Infection Microbiology, 2023)
While Staphylococcus aureus (S. aureus) bacteria are part of the human commensal flora, opportunistic invasion following breach of the epithelial layers can lead to a wide array of infection syndromes at both local and distant sites. Despite ubiquitous exposure from early infancy, the life-long risk of opportunistic infection is facilitated by a broad repertoire of S. aureus virulence proteins. These proteins play a key role in inhibiting development of a long-term protective immune response by mechanisms ranging from dysregulation of the complement cascade to the disruption of leukocyte migration. In this review we describe the recent progress made in dissecting S. aureus immune evasion, focusing on the role of the superantigen, staphylococcal protein A (SpA). Evasion of the normal human immune response drives the ability of S. aureus to cause infection, often recurrently, and is also thought to be a major hindrance in the development of effective vaccination strategies. Understanding the role of S. aureus virulence protein and determining methods overcoming or subverting these mechanisms could lead to much-needed breakthroughs in vaccine and monoclonal antibody development.